Fibonacci lengths of all finite p-groups of exponent p² - Ahmadi, B.; Doostie, H. (Український математичний журнал, 2013)
The Fibonacci lengths of finite p-groups were studied by Dikici and coauthors since 1992. All considered groups are of exponent p and the lengths depend on the Wall number k(p). The p-groups of nilpotency class 3 and exponent p were studied in 2004 also by Dikici. In the paper, we study all p-groups of nilpotency class 3 and exponent p². Thus, we complete the study of Fibonacci lengths of all p-groups of order p⁴ by proving that the Fibonacci length is k(p²). Довжини Фібоначчі скінченних p-rpyn вивчалися Дікічі та співавторами з 1992 року. Всі групи, що розглядалися, були групами експоненти p, а всі довжини залежали від числа Уолла k(p). p-Групи класу нільпотентності 3 i експоненти p були також досліджені Дікічі у 2004 році. У даній статті ми вивчаємо всі p-групи класу нільпотентності 3 і експоненти p². Цим завершується дослідження довжини Фібоначчі всіх p-груп порядку p⁴; при цьому доведено, що довжина Фібоначчі дорівнює k(p²).